Topografias para um inventário cultural: dimensões utópicas em poemas de Izabel Brandão, Bruno Ribeiro e Marlon Silva - Santos, Arenato da Silva (2018)
By inscribing itself within the interfaces between Literary Studies and Critical Studies of Utopia, one of the major motivations underlying the purpose of this dissertation is to ponder the relations between poetry and utopia, highlighting and observing the utopian and/or dystopian reconfigurations in culture, starting from the study of thematic and formal recurrences related to literary utopianism as a genre. This work analyses poems by Izabel Brandão (2013), Bruno Ribeiro (2014) and Marlon Silva (2011), from the perspective of their utopian and/or dystopian forms, functions and contents. Stemming from Thomas More (1998), founding author of literary utopianism, the key considerations are based on theories regarding the concepts of utopia (COELHO,1985; MÜNSTER, 1993; HARVEY, 2000; BLOCH, 2005); and dystopia (MOYLAN, 2 016). The discussion about the interfaces between poetry and utopia has its bases on studies by Oliveira (2010), Franco Júnior (1998a, 1998b) and Santos (2006). Thus focusing on readings of poems composed by these authors, this study contributes to the visibility and appreciation of contemporary local poetic production, thus bringing to the heart of ongoing discussions works and authors who are littleknown by the larger public or, otherwise, known only within the academic field; it also contributes to the construction of an analytical apparatus for approaching a utopian and/or dystopian poetics in culture, helping consolidate, in doing so, the mapping of contemporary utopianisms in Alagoas.